Revenue Statistics in Africa: Rwanda (Edition 2017) (OECD Tax Statistics, 2017)
This dataset contains tax revenue collected by Rwanda. It provides detailed tax revenues by sector (Supranational, Federal or Central Government, State or Lander Government, Local Government, and Social Security Funds) and by specific tax, such as capital gains, profits and income, property, sales, etc